Lifetime productivity: Genetic study of longevity and its associations with economically important traits in dairy buffaloes - Aspilcueta-Borquis, Rusbel Raul; Seno, Leonardo de Oliveira; Araujo Neto, Francisco Ribeiro de; Santos, Daniel Jordan de Abreu; Hurtado-Lugo, Naudim Alejandro; Tonhati, Humberto [UNESP] (Elsevier, 2022)
To increase the permanence of animals in dairy herds by decreasing involuntary slaughter contributes to the development of a sustainable production system. This sustainability is the result of reduced sanitary costs, increased productive life of females, and increased animal welfare. This study aims to estimate genetic parameters for productive lifespan (PL) and functional productive life (FPL) associated with the following economically important traits: milk (MY), fat (FY), and protein yields (PY); fat percentage (%F) and protein percentage (%P); age at first calving (AFC); and calving interval (CI) in dairy buffaloes. The productive lifespan was defined at 48 (PL48), 60 (PL60), and 72 (PL72) months of age. The (co) variance components were estimated using the multi-trait model and the Gibbs2F90 software. To determine the selection effects for FPL72, a deterministic simulation was performed to obtain the direct and indirect genetic gains. Selection indices were calculated, including or excluding FPL72, considering the economic values of dairy cattle (economic values for 2010 and 2014 – EV10 and EV14). The estimates of heritability of PL and FPL were low, ranging from 0.09 to 0.15 for PL48 and PL72, respectively, and from 0.12 to 0.18 for FPL48 and FPL72, respectively. The genetic correlations of PL or FPL with the productive traits (MY, FY, and PY) ranged from low to moderate, obtaining values between 0.07 (PL48/MY) and 0.34 (FPL72/MY). The genetic correlations of PL or FPL with %F and %P presented negative values, with some values reaching near zero. The estimated genetic correlations between PL or FPL and the reproductive traits ranged from 0.16 (FPL72/CI) to -0.11 (PL48/AFC). Regarding the genetic gain for FPL72, the results showed that indirect selection can be achieved by selecting the productive traits. The expected responses for EV10 and EV14 ranged from +$102 to $147. The results indicate that FPL should be considered in water buffaloes to allow identifying efficient animals. Thus, this trait should be considered in genetic improvement programs.
Keywords: Bubalus bubalis; Correlated responses; Genetic parameters; Selection index; Stayability